2010
DOI: 10.1097/pai.0b013e3181b16b88
|View full text |Cite
|
Sign up to set email alerts
|

Sox2 Expression in Pulmonary Non-small Cell and Neuroendocrine Carcinomas

Abstract: Sox2 is a transcription factor that regulates embryonic stem cell pluripotency and drives commitment of airway precursor cells to basal-type and neuroendocrine cells in the developing lung. In cancer, Sox2 has been associated with a "stemness" phenotype that predicts for poor outcomes. We examined Sox2 expression in pulmonary neoplasms with respect to tumor type and differentiation, in comparison with conventional markers. Immunohistochemistry for Sox2, p63, CK5/6, and thyroid transcription factor-1 was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
76
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(82 citation statements)
references
References 29 publications
4
76
0
2
Order By: Relevance
“…17 In lung cancer, SOX2 amplification and expression can be found in a large subset of squamous cell carcinomas. 9,10,17,18 Though at much lower frequencies, expression of SOX2 has also been reported to occur in adenocarcinomas of the lung. [17][18][19] In vitro studies suggest that SOX2 upregulation induces cell proliferation and anchorage-independent growth in squamous cell lung cancer cell lines.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…17 In lung cancer, SOX2 amplification and expression can be found in a large subset of squamous cell carcinomas. 9,10,17,18 Though at much lower frequencies, expression of SOX2 has also been reported to occur in adenocarcinomas of the lung. [17][18][19] In vitro studies suggest that SOX2 upregulation induces cell proliferation and anchorage-independent growth in squamous cell lung cancer cell lines.…”
mentioning
confidence: 99%
“…9,10,17,18 Though at much lower frequencies, expression of SOX2 has also been reported to occur in adenocarcinomas of the lung. [17][18][19] In vitro studies suggest that SOX2 upregulation induces cell proliferation and anchorage-independent growth in squamous cell lung cancer cell lines. 9,10 Furthermore, SOX2 amplification and expression have been detected in preinvasive lesions of the lung, such as squamous dysplasia and carcinoma in situ.…”
mentioning
confidence: 99%
“…Former studies suggest that overexpression of SOX2 may be an important way to activate the Nanog/Oct4/SOX2 pathway, which promotes tumor cell proliferation and is associated with short survival time of patients in stage I ADC (46). SOX2 is also activated in more advanced SCC tumors as others have reported (23,34). We conclude that SOX2 is activated not only by overexpression, but also through amplification as also mentioned by others (23,47).…”
Section: Discussionmentioning
confidence: 54%
“…The data indicate a discrepancy in the characteristics of SCC and ADC. Current comparative genomic hybridization studies have demonstrated that >90% of SCCs and ~20% of ADCs have copy number gain involving 3q26,4, essentially the same proportions that have been demonstrated to have high level SOX2 expression at the protein level (34). Of note, these studies have found high level amplification only in SCC (45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation